Descripción de los corales aulophyllidos del Viseense y Serpujoviense del área de Adarouch (Marruecos) - Said, Ismail; Rodríguez, Sergio (Coloquios de Paleontología, 2009)
Fourteen species of rugose corals belonging to the family Aulophyllidae from Adarouch (Central Morocco) are described. One species is new, Clisiophyllum macrocolumellatum SAID & RODRÍGUEZ; six species perhaps correspond to undescribed forms, but the scarcity of material or its poor preservation impede confirm it and we maintain them in open nomenclature. Seven species are previously known and broadly distributed in the Palaeotethys during the Viséan and Serpukhovian.